2008
DOI: 10.1039/b718294e
|View full text |Cite
|
Sign up to set email alerts
|

On the effect of donor and acceptor substituents on the behaviour of light-driven rotary molecular motors

Abstract: Light-driven rotary molecular motors based on overcrowded alkenes can be substituted with electron-donating and electron-withdrawing substituents (R = OMe, Cl and CN) in direct conjugation with the central double bond (the axis of rotation) without having a significant influence on the rate-limiting, thermal isomerisation step of their rotary cycle. This indicates that in this system, it is predominantly steric factors that determine the barrier to the thermal helix inversion. In contrast, the quantum yield an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
92
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 48 publications
(102 citation statements)
references
References 45 publications
9
92
1
Order By: Relevance
“…24,44 A major experimental effort has therefore been invested in accelerating the rate-limiting thermal steps of overcrowded alkene-based rotary molecular motors, 18,19,21,[23][24][25]27,28,33 exploring the influence of conformational, steric and electronic factors. From such studies, it has been found that one way of lowering the thermal freeenergy barriers of type IIa motors is to contract the sizes of the rotator and stator by employing a cyclopenta[a]naphthalenylidene rotator and a fluorene stator, as done in type IIb motors.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…24,44 A major experimental effort has therefore been invested in accelerating the rate-limiting thermal steps of overcrowded alkene-based rotary molecular motors, 18,19,21,[23][24][25]27,28,33 exploring the influence of conformational, steric and electronic factors. From such studies, it has been found that one way of lowering the thermal freeenergy barriers of type IIa motors is to contract the sizes of the rotator and stator by employing a cyclopenta[a]naphthalenylidene rotator and a fluorene stator, as done in type IIb motors.…”
Section: Methodsmentioning
confidence: 99%
“…From such studies, it has been found that one way of lowering the thermal freeenergy barriers of type IIa motors is to contract the sizes of the rotator and stator by employing a cyclopenta[a]naphthalenylidene rotator and a fluorene stator, as done in type IIb motors. 23,28 Furthermore, for type IIb motors, using a bulkier stereogenic substituent than methyl has also been found to lower the thermal barriers. 23 Complementing these experimental efforts are a number of computational studies that have offered valuable mechanistic insight into the photochemical steps of overcrowded alkene-based rotary molecular motors, [45][46][47][48][49][50] and also identified other molecules as possible light-driven rotary motors.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Substitution on this position of the motor has no effect on the thermal helix inversion, although the photostationary state is affected by electron donating or withdrawing substituents. 44 In a different molecular motor, the effect of substitution with large alkyl groups was also reported to be minimal, 45 so we do not expect a significant difference in behavior between the motor unit in 12 and compound 1.…”
Section: ■ Introductionmentioning
confidence: 81%